Reconstructing Local Identity and Character Values Through Digital Historical Narratives: A Netnography of TikTok's Telisik Pati Community - Taufikin Taufikin; Gulnaz Fatma (UIN Imam Bonjol Padang, 2026)
The development of digital space has led to local historical narratives being increasingly consumed by the younger generation, yet these narratives are not yet fully understood as a platform for character building. This situation has created a gap between the potential of digital historiography as a medium for teaching values and its practical application. This study aims to understand how historical narratives are produced by the TikTok account Telisik Pati shape character values through interactions within the online community. Using a netnographic approach, the study analyzed 19 videos and thousands of comments from October 2024 to December 2025. Digital observation, thematic analysis, and contextual interpretation were used to reveal the value patterns that emerge in the content and user responses. The results of the study reveal four main patterns of character formation: moral-religious values manifested through historical reflection; solidarity and guyub-rukun (harmony) reinforced by local identity narratives; the appreciation of Javanese traditions and ethics revitalized through digital dialogue; and ecological awareness that grows from the connection between history and natural space. Public interaction reveals a collaborative process of value internalization, in which historical narratives function not only as information but also as emotional and pedagogical media. The discussion confirms that digital historiography plays a significant role as a character-building tool within a strong local culture. This study concludes that digital historical narratives can be an effective strategy for strengthening character values in the social media era. The implications include the utilization of historical content for character education and the reinforcement of local identity in digital communities.